The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3122/jabfm.2018.04.180008
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity Trends in United States Adults, 1988–2014

Abstract: Importance:The simultaneous presence of multiple conditions in one patient (multi-morbidity) is a key challenge facing primary care.Objective: The purpose of this study was to determine the prevalence of multi-morbidity and to document changes in prevalence during the last 25 years.Design/Setting: Cross-sectional study using multiple years (1988 -2014) Results: A total of 57,303 individuals were surveyed regarding the presence of multi-morbidity in separate surveys spanning 1988 -2014. The overall current pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
178
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(194 citation statements)
references
References 44 publications
11
178
4
1
Order By: Relevance
“…1 The US National Health and Nutrition Examination Survey 2013-2014 found that among 5541 people aged ≥20 years, the prevalence of multimorbidity (two or more chronic diseases) was 59.6% overall, 37.5% in those aged 20-44 years, 70.6% in those aged 45-64 years and 91.5% in those aged ≥65 years. 2 In addition, the proportion with four or more chronic diseases was 6.0%, 26.4% and 55.6% for those aged 0-44 years, 45-64 years and ≥65 years, respectively. According to a survey of 3737 people aged ≥45 years in China, the prevalence of multimorbidity (two or more chronic diseases) was 34.9% in those aged 45-59 years, 54.9% in those aged 60-69 years and 60.6% in those aged ≥70 years.…”
Section: Epidemiology Of Multimorbiditymentioning
confidence: 94%
See 3 more Smart Citations
“…1 The US National Health and Nutrition Examination Survey 2013-2014 found that among 5541 people aged ≥20 years, the prevalence of multimorbidity (two or more chronic diseases) was 59.6% overall, 37.5% in those aged 20-44 years, 70.6% in those aged 45-64 years and 91.5% in those aged ≥65 years. 2 In addition, the proportion with four or more chronic diseases was 6.0%, 26.4% and 55.6% for those aged 0-44 years, 45-64 years and ≥65 years, respectively. According to a survey of 3737 people aged ≥45 years in China, the prevalence of multimorbidity (two or more chronic diseases) was 34.9% in those aged 45-59 years, 54.9% in those aged 60-69 years and 60.6% in those aged ≥70 years.…”
Section: Epidemiology Of Multimorbiditymentioning
confidence: 94%
“…Developed countries have experienced increases in the older adult population, as well as in life expectancy. The prevalence of various chronic diseases increases with age, and the number of older adults who simultaneously have multiple chronic diseases (multimorbidity) is increasing . In older adults, functional decline is observed in most organs, including the cardiac, respiratory and renal functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 During 2013 to 2014, data from the National Health and Nutrition Examination Survey (NHANES) indicated an overall prevalence of Ն2 comorbidities was 60%; 39% had Ն3, and 23% had Ն4 -significantly higher than the prevalence in 1988 (46% with Ͼ2 comorbidities). Whites had the greatest increase, and obesity, its causes, and its comorbidities are likely substantial underlying factors.…”
Section: Morbidity and Obesitymentioning
confidence: 99%